2014
DOI: 10.1111/icad.12094
|View full text |Cite
|
Sign up to set email alerts
|

Logging in boreal field‐forest ecotones promotes flower‐visiting insect diversity and modifies insect community composition

Abstract: 1. Mitigation tools aimed at counteracting the loss of farmland insect diversity and associated ecosystem services are usually conducted on cultivated fields. Possibilities of managing field-forest ecotones for biodiversity have been rarely discussed, despite their importance for flower-visiting insects.2. The effectiveness of logging in enhancing three aspects of insect diversity (bumblebee abundance, total species richness, and habitat specialist butterfly abundance) and changes in insect community compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 61 publications
3
24
0
1
Order By: Relevance
“…The beneficial effect of open spaces created by clear cuts can be related to the pace of plant cover regeneration in the cleared site. This was shown in Finland where significant positive effects on butterfly and bee abundance and diversity were observed mostly in the second year after disturbance and correlated with the flower and shrub coverage [33]. In our study, the lack of effect could therefore be connected to a low abundance and diversity of floral resources (Česonienė et al, unpublished results), since relatively recent logging negatively impacted the structure of understory vegetation with excessively short time for it to recover.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The beneficial effect of open spaces created by clear cuts can be related to the pace of plant cover regeneration in the cleared site. This was shown in Finland where significant positive effects on butterfly and bee abundance and diversity were observed mostly in the second year after disturbance and correlated with the flower and shrub coverage [33]. In our study, the lack of effect could therefore be connected to a low abundance and diversity of floral resources (Česonienė et al, unpublished results), since relatively recent logging negatively impacted the structure of understory vegetation with excessively short time for it to recover.…”
Section: Discussionsupporting
confidence: 53%
“…This indicates that the responses of the local arthropod communities are not necessarily universal and likely depend on factors such as remaining or recovering plant cover or time since disturbance [33]. The response can by highly dynamic and also species-specific [6], which means that further investigations are necessary to address the impact of intensive forest management on various aspects of forest biodiversity.…”
Section: Discussionmentioning
confidence: 99%
“…The management and restoration of remaining semi-natural grasslands is vital, but so is a more holistic landscape approach that also takes into account other potentially valuable herbaceous habitats, such as field margins, forest edges, clear-cuts, power-line corridors, and fallows (Jonason et al, 2010;Berg et al, 2011;Blixt et al, 2015;Korpela et al, 2015;Toivonen et al, 2015;Viljur & Teder, 2016). The management and restoration of remaining semi-natural grasslands is vital, but so is a more holistic landscape approach that also takes into account other potentially valuable herbaceous habitats, such as field margins, forest edges, clear-cuts, power-line corridors, and fallows (Jonason et al, 2010;Berg et al, 2011;Blixt et al, 2015;Korpela et al, 2015;Toivonen et al, 2015;Viljur & Teder, 2016).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Hence, this confirms the proposition by Bergman et al (2014) that this grassland specialists group is truly relying on grassland which does not seem to be the case for larger group of grassland-dependent species. Members of the latter group can be found not only in grassland but in several types of "marginal" habitats (Jonason et al, 2010;Ibbe et al, 2011;Berg et al, 2011;Korpela et al, 2015;Blixt et al, 2015). Franzén and Nilsson (2008) stressed the importance of flowerrich habitats for red-listed pollinating insects and Wallis de Vries et al (2012) identified flower abundance as a crucial factor responsible for widespread decline in butterfly richness.…”
Section: Bees Butterflies and Day-flying Moths Are Relatively Similarmentioning
confidence: 99%